The assessment of serum amylase in patients with type-II diabetes mellitus - Daruwala, Aafrin N.; Patel, Akshali V.; Kachhiya, Shivani M. (International Journal of Research in Medical Sciences, 2023)
Background: Diabetes mellitus (DM) is a metabolic disorder that causes excessively high blood glucose levels. As there is an interrelationship between the functional and anatomical portions of the pancreas, it may affect the exocrine portion as well. Aim of the study was to assess the level of serum amylase and random blood glucose in patients with T2DM compare and correlate it with healthy controls. Methods: This Analytical cross sectional study was conducted in the Parul Sevashram, Hospital, Vadodara. We enrolled 100 type 2 diabetic subjects aged 40 to 60 years and 100 healthy patients to analyze their blood glucose and serum amylase levels. Results: We found statistically sig (P <0.01) lower serum amylase levels in T2DM patients compared to healthy controls. Cases had significantly higher RBS levels than controls. The mean±SD of RBS of group-1 was 142.29±62.296 mg/dl, group-2 was 105.36±23.336 mg/dl. The mean±SD of serum amylase of group-1 was 65.949±29.5554 u/l, group-2 was 87.82±42.4896 u/l. In our study we found weak negative correlation between Plasma blood glucose and serum amylase in cases, having statistical sig P value= 0.0001 and r value was -0.384. Conclusions: The results of our study shown that in T2DM cases, where the RBS level was higher; the serum amylase activity was significantly lower. This represented a malfunction in the pancreas endocrine-exocrine axis, as any pathological change that impacted any section of an organ would affect the surrounding area of that organ functionally.